Perlindungan Hukum Terhadap Konsumen Rokok Elektrik - Wiwin Muchtar Wiyono; Suryati; Nurlaeli Sukesti Ariani Nasution (Wijayakusuma Law Review, 2021)
The circulation of goods and/or services in society at this time also affects the development of cigarette products,both kretek cigarettes, white cigarettes, cigars and even the development of electric cigarettes. The governmenthas issued many regulations related to smoking. One of the most popular cigarettes in society is the electriccigarette which aims to protect consumers from harm. However, e-cigarettes also contain dangers that manyconsumers are not aware of. The form of protection for cigarette consumers has been issued PP No. 109 of 2012concerning the Safety of Materials Containing Addictive Substances in the Form of Tobacco Products for Health.The PP also applies to e-cigarettes. This study uses a normative juridical method, with secondary data as the maindata in the form of legislation, and related literature. The data were analyzed qualitatively. In general, inconsumer protection law there are several principles of responsibility, namely the principle of responsibility basedon the element of error/negligence, the principle of the presumption of being responsible (presumption ofliability), the principle of the presumption of not always being responsible (presumption of nonliability) and theprinciple of absolute responsibility (strict liability). The responsibility of business actors to consumers using ecigarettes is included in the principle of presumption of liability, known as a reverse proof system where businessactors as defendants are always considered responsible for all losses suffered by consumers until they can provethat the business actor not guilty